2016
DOI: 10.1159/000444643
|View full text |Cite
|
Sign up to set email alerts
|

Association between Single-Nucleotide Polymorphisms of the <b><i>hOGG1,</i></b><b><i>NEIL1,</i></b><b><i>APEX1, FEN1,</i></b><b><i>LIG1,</i></b> and <b><i>LIG3</i></b> Genes and Alzheimer's Disease Risk

Abstract: Background: One of the factors that contribute to Alzheimer's disease (AD) is the DNA damage caused by oxidative stress and inflammation that occurs in nerve cells. It has been suggested that the risk of AD may be associated with an age-dependent reduction of the DNA repair efficiency. Base excision repair (BER) is, among other things, a main repair system of oxidative DNA damage. One of the reasons for the reduced efficiency of this system may be single-nucleotide polymorphisms (SNP) of the genes encoding its… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(9 citation statements)
references
References 60 publications
1
8
0
Order By: Relevance
“…Creb1 and its binding partners play a well-documented critical role in nervous system development and in the protective response to neuron stressors 62 . Creb1 dysregulation is likely to be involved in Alzheimer’s disease 65 , Parkinson’s disease, Huntington’s disease, Rubinstein-Taybi syndrome, ischemia, alcoholism, schizophrenia, addiction, and depression (reviewed in Sakamoto et al 62 and Thakur et al 66 ). In the mature CNS, Creb1 mediates transcription of multiple factors required for neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
“…Creb1 and its binding partners play a well-documented critical role in nervous system development and in the protective response to neuron stressors 62 . Creb1 dysregulation is likely to be involved in Alzheimer’s disease 65 , Parkinson’s disease, Huntington’s disease, Rubinstein-Taybi syndrome, ischemia, alcoholism, schizophrenia, addiction, and depression (reviewed in Sakamoto et al 62 and Thakur et al 66 ). In the mature CNS, Creb1 mediates transcription of multiple factors required for neuronal survival.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that downregulation of NEIL1 expression in the lymphocytes of LOAD patients is not due to the methylation status of NEIL1 promoter [33]. In another study, Kwiatkowski et al conducted SNP genotyping assay on peripheral blood samples from LOAD patients and controls, and suggested that the combination of NEIL1 rs4462560 (p = 0.511) and 8-oxoguanine DNA glycosylase gene ( OGG1 ) rs1052133 (p = 0.535) increases the risk of LOAD (OR = 2.24, 95% CI = 1.36–3.91, p = 0.041) [36]. In the present study, the NGS primers do not cover NEIL1 rs4462560 location (Table 1, S1 Fig and S1 Table).…”
Section: Discussionmentioning
confidence: 99%
“…However, not all BER genes have been screened for their association with reduced BER capacity in LOAD patients and with LOAD development using targeted next generation sequencing (NGS) technology. Several studies have demonstrated no association between predominant variant of 8-oxoguanine DNA glycosylase ( OGG1 ) gene, Ser326Cys, and LOAD risk [36,37,39,43]. Another mutations of OGG1 , A53T, A288V and C796del, that cause a decrease in OGG1 activity have been identified in brain tissues of LOAD patients, but not in control tissues [41,42].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…DNA repair and antioxidant enzymes (defense systems) protect against the development of diseases. There are many published studies on antioxidant enzyme activity, DNA repair enzymes and OS‐related diseases . These defense systems have important roles in the development of IS.…”
Section: Introductionmentioning
confidence: 99%